Attitudes of Erciyes University Students to the Use of Animals in Research - Ozen, Rahsan; Ozen, Abdullah (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
This study was conducted to determine attitudes to the use of animals in research of Erciyes University students attending Faculties of Biology, Civil Engineering, Fine Arts and Veterinary Medicine in the 2005-2006 academic year. Seven hundred and thirty nine (82.2%) of the 899 students enrolled in these faculties were reached by a survey. Several results were found: (a) Of all survey participants 59.1% displayed a zoocentric attitude (4>). (b) Male students (P<0.001), civil engineering students (P<0.001) and survey participants brought up in a town or district (P<0.01) displayed a more anthropocentric attitude and were in support of animal experiments. (c) The majority of the survey participants expressed their agreement with the opinion that compared to alternative (non-animal) methods, animal experiments are easier, more scientific, more common, less costly, and more reliable, whereas they also stated that they disagreed with the opinion that animal experiments are more humane.
Erciyes üniversitesi ö?rencilerinin araştırmalarda hayvan kullanımına yaklaşımları
Keywords: Animal experimentation; Animal use in researches; Animal ethics; Erciyes University